Whump, Slosh, Slosh, Slosh—Filling the Crater That Did in the Dinosaurs - Richard Norris (AGU Advances, 2020)
Abstract Drilling into the Chicxulub crater (Yucatan, Mexico) reveals the dramatic aftermath of the dinosaur‐killing meteorite impact. Previous views of this event have mainly come from places well away from Ground Zero, where we see the extinction of ~70% of life, the fallout of a globe‐spanning ejecta cloud, and the slumps and tsunamis that accompanied one of the biggest terrestrial earthquakes ever. The new view from the crater in a drill core records the collapse of the shattered and melted crater walls, the flood of the ocean back into the submarine crater, and the formation of hot vents over the pool of melt rock. The record shows that decades to centuries after the impact, the calm tropical marine lake was taken over by red tides and animals that colonized the previously sterile crater floor. The exact timing of appearance of the first newly evolved species is hard to pin down but probably occurred within a few centuries to several millennia based on evidence from the intensity of burrowing and estimates of sedimentation rates.